Synthesis and properties of crosslinked poly(arylene ether nitriles) containing pendant phthalonitrile. Issue 3 (8th May 2012) - Yang, Jian; Yang, Xulin; Zhan, Yingqing; Zou, Yanke; Zhao, Rui; Liu, Xiaobo
Abstract: In this study, poly(arylene ether nitriles) containing pendant carboxyl groups (PEN‐COOH) was first synthesized via nucleophilic aromatic substitution reaction from phenolphthalein, hydroquinone and 2, 6‐dicholorobenzonitrile. Then, poly(arylene ether nitriles) with pendant phthalonitrile groups (PEN‐CN) was obtained via the Yamazaki–Higashi phosphorylation route from 4‐(4‐aminophenoxy)phthalonitrile (APN) with PEN‐COOH in the presence of CaCl2, thus the phthalonitrile as pendant groups in PEN‐CN were easily crosslinked by further thermal treatment. The effect of crosslinking density on the thermal stabilities, dielectric properties and water absorption of the PEN‐CNs was investigated. These results showed that the T g of PEN‐CN was improved from 182 to 213°C, dielectric constant (ε) was increased from 3.1 to 3.9, and dielectric loss (tan δ) was decreased from 0.090 to 0.013 at 1 kHz. The water absorption of PEN‐CNs after thermal crosslinking was <1.01 wt %, which showed excellent water resisting property. Therefore, this kind of poly(arylene ether nitriles) containing pendant phthalonitrile could be a good candidate as matrix resins for high‐performance polymeric materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :